The ripple effect: A spillover model of the detrimental impact of work–family conflict on job success. (28th December 2016) - Wayne, Sandy J.; Lemmon, Grace; Hoobler, Jenny M.; Cheung, Gordon W.; Wilson, Morgan S.
Summary: Exploring the role of both the employee and supervisor, we tested a model of how cognition‐based work‐to‐family conflict manifests itself in the workplace, impacting employee job success. Based on conservation of resources theory and the concept of loss spirals, we hypothesized that when an employee's work interferes with family demands, the resulting work‐to‐family conflict spills over to the work domain via employee emotional exhaustion. We further argued that the behavioral manifestation of employee emotional exhaustion in the workplace is low employee engagement, as assessed by the supervisor. Drawing on signaling theory, we proposed that supervisor assessments of employee engagement are related to promotability, performance ratings, and salary. Work scheduling autonomy, as a boundary condition, is examined as a resource that attenuates these relationships. Data collected from 192 employee–supervisor dyads of a Fortune 1000 company, as well as performance ratings and salary obtained from company records 9 months later, indicated support for our conceptual model. Future research examining employee work–family conflict and job outcomes is discussed. Copyright © 2016 John Wiley & Sons, Ltd.